Pemerkasaan Peranan Diwan al-Sadarat dalam Pentadbiran Mughal Era Awrangzib (1658-1707): Revitalization of Diwan al-Sadarat’s Roles in Mughal Governance During Awrangzib’s Reign (1658-1707) - Mohamad Zulfazdlee Abul Hassan Ashari (Online Journal of Research in Islamic Studies, 2021)
Diwan al-Sadarat is one of the important institutions which supervise the aspects of education and religion in Mughal Empire. Although the role of Diwan al-Sadarat have deteriorated before, but the revitalization efforts were implemented after Awrangzib ruled the Mughal Empire in 1658. Based on this statement, this article aims to examine Awrangzib’s efforts to revitalize Diwan al-Sadarat for ensuring this institution will play the vital and significant role as a main department of the empire. This study applied a qualitative methods like historical study and content analysis to collect and analyze data base on primary and secondary sources. The findings of research show that Awrangzib succeeded in revitalizing the role of Diwan al-Sadarat which driven by various factors like his commitment and political will to restore the Diwan al-Sadarat, the involvement of Muslim scholars in supporting the ruler, and the restructuring the governance of Diwan al-Sadarat. In that reign, Diwan al-Sadarat played a significant role in enhancement of education and religion, like supervised the development of education in India, provided the grants for educational institutions, managed the religious officers appointment and madad al-ma‘ash.